Design principles of the common Gly-X6-Gly membrane protein building block - Kiana Golden; Catalina Avarvarei; Charlie T. Anderson; Matthew Holcomb; Weiyi Tang; Xiaoping Dai; Minghao Zhang; Colleen A. Mailie; Brittany B. Sanchez; Jason S. Chen; Stefano Forli; Marco Mravic (Proceedings of the National Academy of Sciences, 2025)
Protein behavior in lipids is poorly understood and inadequately represented in current computational models. Design and prediction abilities for bilayer-embedded molecular structures may be improved by characterizing membrane proteins’ most frequent, favored structural features to glean both context-specific and general principles. We used protein design to proactively interrogate the sequence–structure relationship and stabilizing atomic details of two highly prevalent antiparallel transmembrane (TM) motifs with Small-X 6 -Small consensus sequences. A fragment-based data-mining and sequence statistical inference method including cross-evolutionary structure-aligned covariance enabled engineering of de novo TM protein assemblies by successfully encoding Gly-X6-Gly and Ala-X6-Ala building blocks. A highly stable glycine-based design’s X-ray structure hosts Cα-H∙∙∙O = C H-bonding alongside extensive backbone-directed van der Waals packing, idealizing features of this motif in Nature. Data-driven design navigates sequence space to directly inquire upon how to encode and stabilize vital membrane protein structural elements, facilitating efficacious construction of lipid-embedded architectures of increasing complexity.